Strategic sport communication - Pedersen, Paul Mark PhD; Laucella, Pamela C. PhD; Kian, Edward (Ted) M. PhD; Geurin, Andrea N. PhD (Human Kinetics, 2017)
Strategic Sport Communication, second edition, explores the sport industry's exciting and multifaceted segment of sport communication. With communication theory, sport literature, and insight from the industry's leading professionals, the text presents a standard framework that introduces readers to the many ways in which individuals, media outlets, and sport organizations work to create, disseminate, and manage messages to their constituents. Using the industry-defining standard of the Strategic Sport Communication Model (SSCM), the text explores sport communication in depth and then frames the three major components of the field: personal and organizational communication, sport media, and sport communication services and support. The second edition includes the following enhancements: a new, expanded chapter titled Integrated Marketing Communication in Sport allows students to explore modern marketing strategy; substantial updates and new information on multiple social media platforms throughout the book elucidate the latest trends; "Sport Communication at Work" sidebars and "Profile of a Sport Communicator" features apply topics and theoretical concepts to real-world situations; key terms, learning objectives, and chapter wrap-ups with review questions, discussion questions, and individual exercises keeps readers engaged and focused; an expanded ancillary package provides tools for instructors to use in course preparation and presentation